2017
DOI: 10.1108/rpj-10-2016-0166
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-printed osseointegrated combined jaw and dental implant prosthesis – a case study

Abstract: Purpose This paper aims to present a new design in the area of basal osseointegrated implant (BOI) for oral and maxillofacial surgery using a patient-specific computer-aided design (CAD) and additive manufacturing (AM) approach. The BOI was designed and fabricated according to the patient’s specific requirement, of maxilla stabilisation and dental fixation, a capacity not currently available in conventional BOI. The combination of CAD and AM techniques provides a powerful approach for optimisation and realisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Most publications about medical models produced with additive manufacturing methods concern the topic of the skeletal system. Apart from this, subgroups were additionally distinguished due to the large number of articles on single structures: the skull [ 4 , 5 ], facial skeleton [ 6 , 7 , 8 ], which apart from reconstructive surgery also includes dentistry and orthodontics [ 9 , 10 ] and the thoracic/rib region. The circulatory system, including publications concerning only the heart or other structures [ 11 , 12 ], and articles concerning the kidneys [ 13 , 14 , 15 ] and liver [ 16 , 17 ], can be classified as more recent publications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most publications about medical models produced with additive manufacturing methods concern the topic of the skeletal system. Apart from this, subgroups were additionally distinguished due to the large number of articles on single structures: the skull [ 4 , 5 ], facial skeleton [ 6 , 7 , 8 ], which apart from reconstructive surgery also includes dentistry and orthodontics [ 9 , 10 ] and the thoracic/rib region. The circulatory system, including publications concerning only the heart or other structures [ 11 , 12 ], and articles concerning the kidneys [ 13 , 14 , 15 ] and liver [ 16 , 17 ], can be classified as more recent publications.…”
Section: Methodsmentioning
confidence: 99%
“…The next stage concerns the design in CAD programs, but it is not a mandatory element. CAD is most often used in the design of guiding instruments [ 10 ], for reconstructions in the craniofacial area, where a template is designed for cutting the bones of the arrow/scapula [ 6 , 7 , 8 ] or when the parallel process of designing the casting mould is taken for the production of models imitating soft tissues in the casting process [ 17 , 22 ]. The methodology at this stage is divided into two paths, depending on the design assumptions, available funds and manufacturing technology.…”
Section: Methodsmentioning
confidence: 99%
“…Craniofacial plates/mesh, made of Ti-6Al-4V, fabricated using EBM technology has shown promising results for skull reconstruction (Wang and Qi 2020;Park et al 2016), Ti-6Al-4V jaw, dental and subperiosteal implant fabricated using DMLS technology demonstrated successful (Jardini et al 2016), dental screw (Tedesco et al 2017) and mandibular implant (Chen et al 2017), spinal implant (Phan et al 2016) and sternum implant (Dzian et al 2018), hip (Wong et al 2015) and knee implant, bone implant (Shuang et al 2016), extravascular stent (Wang et al 2019). Reprinted under copyright CCBY-NC-ND 4.0 license osteointegration circumventing bone regeneration therapies (Malyala et al 2017;Mangano et al 2020). Titanium spinal implant fabricated using EBM and DMLS have enabled reconstruction of cervical spine (Xu et al 2016;Willemsen et al 2019), titanium sternal implant fabricated using DMLS offers progressive treatment for sternal cancer or total sternectomy (Dzian et al 2018), Titanium hip implant fabricated using EBM for successful Hemipelvic Arthroplasty (Zhao et al 2018).…”
Section: D Printing For Biomedical Implantsmentioning
confidence: 99%
“…S K Malyala et al reported the development of a basal osseo-integrated implant that has the ability to be patient specific and provided mass customization for nerves treatment. They reported the analysis of the structure that worked as support for the dental patients [22]. In 2017, AIIMS performed the diagnosis of a patient who needed an immediate implant surgery.…”
Section: B Recent Status Of 3d Printed Implants In Healthcarementioning
confidence: 99%
“…This paper addresses the design requirements for an implant to study GI dysmotility and also presents a miniaturized wireless implant capable of modulating GI motility. Santosh Kumar Malyala et al [22] Osseo-integrated Implant…”
Section: H Cranial Implantsmentioning
confidence: 99%